Effect of Chemical Compounds in Wastes from Essential Oil Distillation on the Activity of E.coli - Mai Anugrahwati; Wiyogo Prio Wicaksono; Rizqy Nurlestari (Airlangga University, 2017)
Effect of chemical compounds in the wastes of essential oil distillation including lime leaves, lemongrass leaves, ylang-ylang flower, and coriander seed on the activity of Escherichia coli has been performed. In this research, observation was done by using microbial fuel cell (using E.coli) with two compartments were connected by nafion membrane and zinc plats were used as electrodes which were connected by copper wire and multimeter. Energy production from the cell was shown from the generated current due to the E.coli's oxidation activity to the substrates (distillation wastes). Results from the research exhibited that chemical compounds in the lime leaves positively affected to the bacterial activity with the generated current present up to 20 µA. It is also observed that mass variation of the substrates significantly affected the current generation. Chemical compounds in the three other wastes were found to be not as effective as lime leaves because from the analysis of their methanol extracts by GC-MS indicated that these contained antibacterial compounds such as octadecanoic acid and rosifoliol. Conclusion from the research was not all of wastes from essential oil distillation have a potency to be used as substrates in the microbial fuel cell as some of these chemicals had an antibacterial property which negatively affected the E.coli bacterial activity in the cell. Keywords : microbial fuel cell, Escherichia coli, waste of essential oil distillation.